Effects of multiple injections on combustion and emissions in a heavy-duty diesel engine at high load and low speed. (December 2020) - Lu, Yingying; Liu, Yize
Advanced multiple injection strategies have been suggested for compression ignition engines in order to meet the increasingly stringent emission regulations. Experiments and simulations were used to study effects of the main-injection mode (times), the post-injection proportion, and timing on combustion and emissions in a heavy-duty diesel engine at high load and constant low speed. The results reveal the following. The NOx emissions of 1main+1post, 2main+1post, and 3main+1post injections are all lower than those of single injection; the higher the number of main-injection pluses, the lower the NOx emissions. Enough main-post injection interval is needed to ensure post and main injections are relatively independent to entrain more fresh air to decrease the soot. Over-retarded post-injection timing tends to increase the soot due to the lower in-cylinder temperature. The combined effects of formation and oxidation determine the final soot. To gain the best trade-off of NOx and soot, compared with single injection, for the three multiple injections, the lowest soot emissions are gained at post-injection proportions of 15% and post-injection timings of 25°, 30°, and 35° CA ATDC, with soot reductions of 26.7%, −34.5%, and −112.8%, and NOx reductions of 5.88%, 21.2%, and 40.3%, respectively, for 1main+1post, 2main+1post, and 3main+1post injections.